Mental Paper Folding Performance Following Penetrating Traumatic Brain Injury in Combat Veterans: A Lesion Mapping Study - Glass, Leila (Oxford University Press, 2013)
Mental paper folding is a complex measure of visuospatial ability involving a coordinated sequence of mental transformations and is often considered a measure of mental ability. The literature is inconclusive regarding the precise neural architecture that underlies performance. We combined the administration of the Armed Forces Qualification Test boxes subtest measuring mental paper folding ability, with a voxel-based lesion symptom mapping approach to identify brain regions associated with impaired mental paper folding ability. Using a large sample of subjects with penetrating traumatic brain injury and defined lesions studied over 2 time points, roughly 15 and 35 years post-injury, enabled us to answer the causal questions regarding mental paper folding impairment. Our results revealed that brain injury significantly exacerbates the decline of performance on mental paper folding tasks over time. Our study adds novel neuropsychological and neuroimaging support for parietal lobe involvement; specifically the right inferior parietal lobule (Broadmann's Area [BA] 40) and the left parahippocampal region (BAs 19, 36). Both areas were consistently associated with mental paper folding performance and demonstrate that the right parietal lobe and the left parahippocampal gyrus play an integral role in mental paper folding tasks.